Effects of antipsychotics on D3 receptors: A clinical PET study in first episode antipsychotic naive patients with schizophrenia using [ 11C]-(+)-PHNO - Mizrahi, Romina; Agid, Ofer; Borlido, Carol; Suridjan, Ivonne; Rusjan, Pablo; Houle, Sylvain; Remington, Gary; Wilson, Alan A.; Kapur, Shitij (Schizophrenia research, 2011)
Most antipsychotics are thought to have an effect on D 2 and D 3 receptors, although their D 3, versus D 2 binding has not been clearly established in vivo in humans. However, the development of [ 11C]-(+)-PHNO now permits the differentiation of antipsychotic activity on these two receptor subtypes. In this study we examined the effects of antipsychotics on D 2 and D 3 receptors by comparing [ 11C]-(+)-PHNO in D 2-rich (caudate, CAU and putamen, PUT), mixed (ventral striatum) and D 3-rich (globus-pallidus, GP and substantia nigra, SN) regions before and after the initiation of antipsychotic medication. The investigation therefore represents a longitudinal within-subject follow-up design wherein antipsychotic-naive patients with schizophrenia spectrum disorders were first scanned in a drug-naïve state and then again after ~ 2.5 weeks of antipsychotic treatment (risperidone or olanzapine). Binding potential (non displaceable or BP ND) was obtained to derive estimates of drug occupancy in the identified brain regions. Antipsychotic treatment was associated with the expected occupancies in the D 2-rich regions; unexpectedly though, patients showed a higher, rather than the expected lower, [ 11C]-(+)-PHNO BP ND in the GP and SN despite simultaneous evidence for ongoing D 2 blockade in the other regions (CAU and PUT). In conclusion, patients treated with atypical antipsychotics demonstrated no evidence of D 3 receptor occupancy, but instead possible D 3 up-regulation following short-term treatment. The present findings add to a very limited body of evidence related to D 3 binding in vivo. [ 11C]-(+)-PHNO offer new opportunities for exploring the potential therapeutic significance of the D 3 receptor in schizophrenia and the action of antipsychotics.